1999
DOI: 10.1038/sj.mp.4000485
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene (5-HTTLPR) is not associated with depressive symptomatology in mood disorders

Abstract: Disturbances of the serotoninergic neutrotransmitter system have been implicated in the pathogenesis of mood disorders. A functional polymorphism in the upstream regulatory region of the serotonin transporter gene (5-HTTLPR) has been recently reported to be associated with both unipolar and bipolar disorder. In this study, we investigated the possibility that the 5-HTTLPR might be associated with depressive symptomatology in a sample of mood disorder subjects. One hundred and thirty-two psychiatric inpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 32 publications
3
55
0
Order By: Relevance
“…36,45,55 Six papers studied a specific clinical feature of BPD rather than the illness itself. 11,[28][29][30]72,73 Finally, two did not provide enough data to be included in the meta-analyses. 48,59 The 31 papers finally selected reported 43 studies related to the review objective in total since each paper frequently reported several separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…36,45,55 Six papers studied a specific clinical feature of BPD rather than the illness itself. 11,[28][29][30]72,73 Finally, two did not provide enough data to be included in the meta-analyses. 48,59 The 31 papers finally selected reported 43 studies related to the review objective in total since each paper frequently reported several separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate specific cluster depressive symptoms, the HAM-D items were grouped according to the following factors: core (Items 1, 2, 7, 8, 10, 13), sleep (Items 4, 5, 6), activity (Items 7, 8), psychic anxiety (Items 9, 10), somatic anxiety (Items 11, 12, 13), and delusion (Items 2, 15, 20), as described by Serretti et al 17 Both the total and subcategory HAM-D scores were subjected to statistical analysis. Therapeutic response was evaluated by the percentage score reduction in total and subcategory HAM-D scores ((baseline score − 4-week score) × 100/baseline score).…”
Section: Methodsmentioning
confidence: 99%
“…The 5-HTT has been directly implicated in depression by the finding that brain 5-HTT binding density is reduced in brains and platelets of depressed patients (e.g., Nemeroff et al 1994;Malison et al 1998;Mann et al 2000). Moreover, a number of studies have found an association between genetic variation in the regulatory region of the 5-HTT gene and depression (e.g., Battersby et al 1996;Collier et al 1996a,b;Furlong et al 1998;Rees et al 1997;Menza et al 1999; but see Seretti et al 1999). The 5-HTT is also a major target for many antidepressant drug treatments (Blakely et al 1991;Ramamoorthy et al 1993).…”
mentioning
confidence: 99%